In vitro applicability of mixed soy lecithin-based liposomes with added several lipophilic agents as novel delivery systems for delivery of quercetin - Toopkanloo, Sahar Pakbaten; Tan, Tai Boon; Cheong, Ling-Zhi; Liu, Yuanfa; Tan, Chin Ping (Taylor and Francis, 2023)
The study used highly lipophilic compounds to evaluate membrane physical and constitutional changes and vesicle stabilization of mixed soy lecithin (ML)-based liposomes. The in vitro bio-accessibility of novel quercetin (QU)-loaded ML-based liposomes as a function of particle size, polydispersity index (PDI), zeta potential (ZP), different membrane stabilizers, membrane fluidity and encapsulation efficacy (EE) was examined. Three different membrane systems, empty ML-based liposomes (E-LPs), squalene (SQ) loaded LPs (SQ-LPs), and SQ and a combination of β-sitosterol (βS) and stigmasterol (ST) loaded LPs (SQ-βS-ST-LPs), were developed based on optimized formulations using an extrusion method and used to encapsulate QU. The applicability of the ML-based liposomal carriers was tested by means of an in-vitro digestion procedure by applying a 2-phase static in- vitro model of the stomach and small intestine allowing for measurement of the bio-accessibility of ingested QU. Stability comparison of the empty liposomal particles, SQ-LPs and SQ-βS-ST-LPs particles was carried out to determine the most appropriate form of QU-loaded ML-based liposomal formulation. Different formulations were observed to possess different amounts of bio-accessible QU, indicating that membrane additives had profound effect on micellization of QU during Gastro-Intestinal Tract (GIT). Bivariate correlation analysis indicated that the bio-accessibility and EE of QU were strongly linearly correlated (R2 = 0.989), suggesting that QU bio-accessibility depended strongly on the retaining of QU in the ML bilayer, and entrapment capacity of the system. Our results paint a consistent picture in which the vesicle integrity, membrane fluidity and membrane-stabilizing function varied upon changing the membrane lipid composition in the ML-based-liposomes.